Cardiac Function in a Long-Term Follow-Up Study of Moderate and Severe Porcine Model of Chronic Myocardial Infarction. (23rd February 2015) - de Jong, Renate; van Hout, Gerardus P. J.; Houtgraaf, Jaco H.; Takashima, S.; Pasterkamp, Gerard; Hoefer, Imo; Duckers, Henricus J.
Abstract : Background . Novel therapies need to be evaluated in a relevant large animal model that mimics the clinical course and treatment in a reasonable time frame. To reliably assess therapeutic efficacy, knowledge regarding the translational model and the course of disease is needed. Methods . Landrace pigs were subjected to a transient occlusion of the proximal left circumflex artery (LCx) ( n = 6 ) or mid-left anterior descending artery (LAD) ( n = 6 ) for 150 min. Cardiac function was evaluated before by 2D echocardiography or 3D echocardiography and pressure-volume loop analysis. At 12 weeks of follow-up the heart was excised for histological analysis and infarct size calculations. Results . Directly following AMI, LVEF was severely reduced compared to baseline in the LAD group - 17.1 ± 1.6 %, P = 0.009 compared to only a moderate reduction in the LCx group - 5.9 ± 1.5 %, P = 0.02 and this effect remained unchanged during 12 weeks of follow-up. Conclusion . Two models of chronic MI, representative for different patient groups, can reproducibly be created through clinically relevant ischemia-reperfusion of the mid-LAD and proximal LCx.